Combating H1N1: metaphors of war in a Malaysian newspaper - Priyadarshni, R. Lakshmi; Mohd Kasim, Zalina; Mohamad Ali, Afida (Universiti Putra Malaysia Press, 2017)
In April 2009, reports of a new strain of a deadly flu virus emerged in Mexico. The scarcity of information available on this new threat can be observed clearly in the language used in the news reports. This study investigates the use of conceptual metaphors of the Influenza A (H1N1) pandemic in the newspaper and how these metaphors helped to construct the notion of a pandemic in the media. Metaphors of illness and disease are a prominent tool in the discourse of disease in the news. The conceptual metaphor theory by Lakoff and Johnson (1980) was utilized as a framework in this study to investigate the coverage of the pandemic in the newspaper. The data was extracted from a corpus of news reports from The New Straits Times Malaysia from April 2009 to August 31, 2009 when the disease was at its peak. The results of the study yielded various metaphorical linguistic expression of war and construction of the pandemic in the news. Metaphors of war were found to be prominent, and it had a rhetorical function in helping to structure and control the situation. By highlighting certain aspects of war, the concept of disease was given a form and structure and thus, made it more tangible and controllable.